The results of the science of this project on data drive agronomy work create a massive opportunity for climate services to optimize Maize management in Mexico - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Together with the MasAgro initiative in Mexico, the data-driven agronomy team determined through the analysis of historical data, the main limiting factors of the yield per region to guide the design of site-specific management recommendations. The drivers of productivity in some regions in Mexico changed according to the regions